THE LIFESTYLE OF SINGLE MOTHERS IN THE EAST COAST OF MALAYSIA: THE IMPACT ON THEIR HEALTH AND WELLBEING - Usman Jaffer; Che Mohd Nasril Che Mohd Nassir; Mohamed Ayaaz Ahmed; Rahmah Ahmad H. Osman; Muhammad Uzaini Zahini Md Zaini; Muhammad Ammar Termizy; Batrisya Afifa Mustaffa; Nur Hidayah Fakhruzzaman; Nurul Arisya Mohd Razani; Nurul Batrisyia Mohd Tarmizi, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study focuses on the health challenges and support mechanisms for single mothers in Malaysia, a demographic that faces unique socio-economic issues. Employing a quantitative approach, the research uses a self-report questionnaire to gather data from 20 single mothers in Kuala Nerus, Terengganu. Analysis reveals that these mothers, predominantly Malay, Muslim, and widowed, face significant health risks including chronic diseases, cardiovascular issues, and psychological strain, exacerbated by factors like financial stress and societal stigma. Physical health challenges among single mothers include an increased prevalence of chronic diseases due to stress and lack of self-care. The study corroborates global trends of health deterioration in single parents, with a specific focus on conditions like back pain, chest infections, and cardiovascular issues. Psychological wellbeing is also a critical concern, affected by factors such as sleep disturbances, financial stress, and societal perceptions. Government initiatives like BKIT provide financial support, but often fall short of addressing the complex needs of this demographic. Community support, while advocated by Islamic teachings, shows a gap in practical implementation. The study highlights the need for more effective strategies to enhance community support. The research uncovers that the number of years without a spouse significantly impacts the financial and overall well-being of single mothers. The limited financial resources affect their access to healthcare and their ability to afford essential treatments. Social support systems in Malaysia are found to be lacking, with non-governmental organizations playing a crucial role in advocacy and support. The study concludes that single mothers in Malaysia face multifaceted challenges that require holistic approaches from government, researchers, and society. The paper proposes expanding research to include diverse demographic representations, longitudinal studies, and qualitative exploration of religiosity. The recommendations emphasize the need for a comprehensive understanding of the experiences and challenges of single mothers, advocating for more inclusive and supportive environments.